S3 Clinical cultures and the sensation of breathlessness. (15th November 2017) - Macnaughton, J; Oxley, R; Rose, A
Abstract : Introduction and Objectives: Our Wellcome Trust funded project, the Life of Breath, takes as its starting point the problem of symptom discordance between clinically measured lung function and patient experience. Clinicians have long recognised the influence of thoughts and emotions on symptom of breathlessness. Recent work in neuroscience, exemplified in the 'multidimensional model' of breathlessness proposed by Lansing et al., 1 has developed this as a material concern, although it leaves unexamined the social, cultural and linguistic fields at work in such thoughts and emotions. This paper proposes to extend the multidimensional model to take into account the wider dimensions of life experience informing the sensation of breathlessness. Methods: We take an interdisciplinary approach that combines material from cultural contexts, clinical accounts and ethnographic work. Cultural readings and ethnographic work demonstrate that breathlessness is imagined and expressed in very different ways outside the clinical context. This corroborates clinical accounts about the significant role background culture has in determining how the symptom of breathlessness is expressed, understood and examined. Nevertheless three clinical cultures overwhelmingly determine contemporary responses to breathlessness: neuroscience, hospital specialist medicine and palliative care. We describe these cultures and argue that no single approach is enabling progress for patients. Results: Our interdisciplinary approach extends understandings of the experience of breathlessness by challenging the linear relationship between sensation and affect described by Lansing. Our findings cluster under three main headings: 1) the language of breathlessness; 2) breathlessness as analogy; and 3) breath awareness, including rhythm. Conclusions: Our research opens out the potential for wider explorations of the symptom of breathlessness that offer an explanation for symptom discordance. Our findings on language suggest reasons for the current poor uptake of pulmonary rehabilitation, and our research on the relationship between experience and sensation point to the potential value of new approaches that might be more acceptable to patients. Reference: Lansing RW, Gracely RH, Banzett RB. The multiple dimensions of dyspnea, review and hypothesis. Respiratory Physiology and Neurobiology 2009;167(1):53–60.